MENUJU GOOD GOVERNANCE DALAM PELAKSANAAN REKOMENDASI OMBUDSMAN REPUBLIK INDONESIA (STUDI KASUS DWELLING TIME DI EMPAT PELABUHAN INDONESIA) - Steffi Seline Maryanne Ginting; Faisal Akbar; Pendastaren Tarigan; Jusmadi Sikumbang (Universitas Sumatera Utara, 2016)
ABSTRACT In the case of acceleration dwelling time, the Ombidsman of the Republik of Indonesia( ORI ) escort up to the President and followed up for the improvement of public service in the port. ORI, as a bridge between the aspirations of the people with the public services and / public officials. The recommendations should be implemented in the public interest. Public services into spears ideals of good governance in a country. Where the law No. 25 of 2009 on the Public Service, in addition to aiming at being the protection and legal certainly for the people in the realm of public services, as well as the certain of the organization so that the public in accordance with the principles of good governance. Keywords : good governance , Ombidsman, dwelling time